Billions of drops in millions of buckets : why philanthropy doesn't advance social progress - Goldberg, Steven H., 1954- (Hoboken, N.J. : John Wiley & Sons, 2009)
Praise for BILLIONS OF DROPS in MILLIONS OF BUCKETS. "Billions of Drops in Millions of Buckets provides a bracing and original look at philan-thropy that offers a much-needed corrective to conventional wisdom. Steve Goldberg combines a resolve to understand why so much philanthropy accomplishes so little enduring social change with a timely and serious proposal to reinvigorate nonprofit capital markets through the simplest of insights: getting more of the money to where it can do the most good. This book will change how forward-looking philanthropists, foundations, and policymakers think
Prelude: "The great recession" -- Preface -- The disheartening problem of "scale" -- The American underclass -- Fragmentation -- Intermediation -- Growth capital -- A performance-based funding market -- Prediction markets -- The Impact Index -- Crossing the fundraising chasm.
Includes bibliographical references and index.
Print version record.
English.
John Wiley and Sons
Keywords: Endowments -- Economic aspects -- United States; Endowments -- United States -- Management; Nonprofit organizations -- United States -- Management; Fondations -- z; Fondations -- x; Associations sans but lucratif -- x; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare; Endowments -- Economic aspects; Endowments -- Management; Nonprofit organizations -- Management; United States